2020
DOI: 10.5815/ijisa.2020.06.03
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Sign Language Recognition System Based on Wi-Fi CSI

Abstract: Many sensing gesture recognition systems based on Wi-Fi signals are introduced because of the commercial off-the-shelf Wi-Fi devices without any need for additional equipment. In this paper, a deep learning-based sign language recognition system is proposed. Wi-Fi CSI amplitude and phase information is used as input to the proposed model. The proposed model uses three types of deep learning: CNN, LSTM, and ABLSTM with a complete study of the impact of optimizers, the use of amplitude and phase of CSI, and prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…SignFi [3] achieved the average recognition accuracy of 98.01%, 98.91%, 94.81%, and 86.66% in the lab276, home276, lab + home276, and lab150, respectively. In 2020, reference [31] compared the three types of deep learning: long shortterm memory (LSTM), CNN, and attentive bi-directional LSTM (ABLSTM). Te experimental results showed that the CNN model had the best recognition performance on the SignFi dataset.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…SignFi [3] achieved the average recognition accuracy of 98.01%, 98.91%, 94.81%, and 86.66% in the lab276, home276, lab + home276, and lab150, respectively. In 2020, reference [31] compared the three types of deep learning: long shortterm memory (LSTM), CNN, and attentive bi-directional LSTM (ABLSTM). Te experimental results showed that the CNN model had the best recognition performance on the SignFi dataset.…”
Section: Related Workmentioning
confidence: 99%
“…We obtained the raw CSI data from the SignFi dataset in Figure 2. Te magnitude and phase of each raw CSI sample can be extracted, normalized, and transformed into a CSI image of size 200 × 60 × 30 as described in [3,31]. Unlike the abovementioned literature, we do not denoise and unwrap the amplitude and phase information.…”
Section: System Overviewmentioning
confidence: 99%
See 3 more Smart Citations